Private banking service for foreign citizens and foreigners in Finland; opportunities, risks and instructions for handling the customer relationship - Kumpulainen, Jari (Saimaan ammattikorkeakoulu, 2014)
The purpose of this study was to examine what kind of potential foreign citizens and foreigners in general are for private banking service and how possible customer relationships should be managed. The study was commissioned by a bank operating in South Karelia region, which is developing guidelines and instructions for customer relationship management for private banking service for foreigners. The objective for this study was also to consider suggestions from risk management point of view as risk management is a vital part of banking operations. The information for this study was gathered from literature, studies, regulations, newspapers and the Internet. Information is gathered from domestic and international studies made in recent years to acquire the most accurate and up to date information regarding the topic. The results of the study show that there is significant potential in foreign citizens and in foreigners in general for private banking service. As the location of the bank is close to the border there are opportunities for using this potential to advantage when banking services are offered by the regulations. Results also show that services and quality of the service need to be improved in order to provide high quality service for potential customers. Also the promotion of the bank, service and products need to be improved as there are no English language brochures in the company. Results of this study can be applied when writing and developing the service for foreigners and when developing instructions for customer relationship management. Further study is required to clarify legal issues of customer relationship management across the border.